Targeted LV Lead Placement is Feasible and Associated with Enhanced CRT Response - Khan, Fakhar Z. (MD Conference Express, 2011)
Results from the Targeted Left Ventricular Lead Placement to Guide Cardiac Resynchronization Therapy Study [TARGET; ISRCTN19717943] show that targeted left ventricular lead placement not only is feasible but results in enhanced cardiac resynchronization therapy response.